Sympathy, empathy, and compassion: A grounded theory study of palliative care patients' understandings, experiences, and preferences. (May 2017) - Sinclair, Shane; Beamer, Kate; Hack, Thomas F; McClement, Susan; Raffin Bouchal, Shelley; Chochinov, Harvey M; Hagen, Neil A.
Background: Compassion is considered an essential element in quality patient care. One of the conceptual challenges in healthcare literature is that compassion is often confused with sympathy and empathy. Studies comparing and contrasting patients' perspectives of sympathy, empathy, and compassion are largely absent. Aim: The aim of this study was to investigate advanced cancer patients' understandings, experiences, and preferences of "sympathy, " "empathy, " and "compassion" in order to develop conceptual clarity for future research and to inform clinical practice. Design: Data were collected via semi-structured interviews and then independently analyzed by the research team using the three stages and principles of Straussian grounded theory. Setting/participants: Data were collected from 53 advanced cancer inpatients in a large urban hospital. Results: Constructs of sympathy, empathy, and compassion contain distinct themes and sub-themes. Sympathy was described as an unwanted, pity-based response to a distressing situation, characterized by a lack of understanding and self-preservation of the observer. Empathy was experienced as an affective response that acknowledges and attempts to understand individual's suffering through emotional resonance. Compassion enhanced the key facets of empathy while adding distinct features of being motivated by love, the altruistic role of the responder, action, and small, supererogatory acts of kindness. Patients reported that unlike sympathy, empathy and compassion were beneficial, with compassion being the most preferred and impactful. Conclusion: Although sympathy, empathy, and compassion are used interchangeably and frequently conflated in healthcare literature, patients distinguish and experience them uniquely. Understanding patients' perspectives is important and can guide practice, policy reform, and future research.